Pendekatan Sosiologis Pada Cerpen “Merdeka” Karya Putu Wijaya - Aini, Dwi Lutfiah; Widyaningtyas, Hanin Mumtazah Putri; Supena, Ahmad (Innovative: Journal Of Social Science Research, 2025)
This research analyzes Putu Wijaya's short story "Merdeka" as a cultural artifact that reflects and criticizes the social reality of Indonesia after independence. A literary sociology approach is used in this research. Apart from the complex phenomena of anomie and social disintegration, this qualitative analysis concentrates on the representation of unequal social structures and power dynamics. The mismatch between the idealism of heroic struggle and the corrupt and dysfunctional moral-political reality causes serious social disillusionment. Abuse of power by elite groups is proof of this. Ingeniously, this short story reveals ideological disputes about the meaning of "independence" in various contexts, including the most psychological and political. This work functions as a critical sociological document that reveals fundamental contradictions in post-proclamation social conditions through rich, complex and in-depth symbolism, as well as analysis of intergenerational relationships. This work also encourages critical reflection on the true essence of freedom, which is multifaceted and continues to evolve